2005
DOI: 10.1111/j.1365-2826.2005.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Fos Protein Expression in the Neonatal Rat Brain

Abstract: Sex differences in the brain and behaviour are mostly a result of transient increases in testosterone during the perinatal period. Testosterone influences brain development primarily through aromatization to oestradiol and subsequent binding to oestrogen receptors. Although some studies report that steroid hormones regulate the expression of the inducible transcription factor, Fos, in developing brain, it is not known if there is a sex difference in Fos expression. Changes in Fos protein can be used as an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 73 publications
0
28
1
Order By: Relevance
“…In addition, it has been reported that the brain turnover undergo major changes during development (Tucek et al, 1990) and such changes may show genetic variation (Adejumo et al, 2005) as reflected in the sex difference in the WAD. Also, of importance is the recent fact that some studies have indicated the expression of some proteins in the brain to be higher in males than females (Olesen and Auger, 2005) This study has shed light into the metal and total protein level in the brain of two goat breeds in Nigeria and may play a relevant role in future analysis of these values in the brain particularly as it affect the interplay between these metals and proteins and the environment. …”
Section: Discussionmentioning
confidence: 84%
“…In addition, it has been reported that the brain turnover undergo major changes during development (Tucek et al, 1990) and such changes may show genetic variation (Adejumo et al, 2005) as reflected in the sex difference in the WAD. Also, of importance is the recent fact that some studies have indicated the expression of some proteins in the brain to be higher in males than females (Olesen and Auger, 2005) This study has shed light into the metal and total protein level in the brain of two goat breeds in Nigeria and may play a relevant role in future analysis of these values in the brain particularly as it affect the interplay between these metals and proteins and the environment. …”
Section: Discussionmentioning
confidence: 84%
“…More particularly, in the developing rat brain c-fos induction has been used to study the ontogeny of the fear response (Wiedenmayer & Barr, 2001), the functional maturation of the amygdala (Moriceau, Roth, Okotoghaide, & Sullivan, 2004), the maturation of the circadian photicresponse in the suprachiasmatic nucleus (Leard, Macdonald, Heller, & Kilduff, 1994), the development of the stress response (Dent, Smith, & Levine, 2001;Levine, 2002), the ontogeny of the oxygen-sensitive pathway in the medulla oblongata (White, Lawson, & Millhorn, 1994) and the response to neurotoxic insults such as anoxia (Tang, Ringstedt, Pequignot, & Lagercrantz, 2000), hypoxia (Ringstedt, Tang, Persson, Lendahl, & Lagercrantz, 1995), ischemia (Pabello, Tracy, SnyderKeller, & Keller, 2005), exposure to alcohol or cocaine (Mitchell & Snyder-Keller, 2003). Furthermore, c-fos expression has been employed to map brain areas activated during nursing (Hironaka, Shirakawa, Toki, Kinoshita, & Oguchi, 2000) and in the process of sexual differentiation of the brain (Giannakopoulou, Bozas, Philippidis, & Stylianopoulou, 2001;Olesen & Auger, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Ponceau S stains a protein band at approximately 45 kDa and allows for accurate quantification of the amount of total protein bound to a membrane. 11 Ponceau S staining has been shown to correlate well with staining for bactin and allows for accurate quantification of the amount of total protein bound to a membrane. 12 Because the protein band appearing at approximately 45 kDa contains all proteins potentially ranging from 43-47 kDa, normalizing to this band takes into account a multitude of proteins.…”
Section: Methodsmentioning
confidence: 99%